Marketing Mix Implementation on Sales Levels - Qibtiyana, Mariyatul; Hapzi Ali (Dinasti International Journal of Management Science, 2024)
Marketing mix is a tactical tool for companies in establishing a strong position in the market. The marketing mix combines four main elements: product, price, place, and promotion, to achieve the company's marketing goals and provide value to consumers. This article outlines the importance of each element in achieving optimal sales levels. Through data collection and analysis methods, it is concluded that effective implementation of the marketing mix can increase sales and the company's position in the market.